Reliability of Automated Biochemical Identification of Burkholderia pseudomallei Is Regionally Dependent - Podin, Yuwana; Kaestli, Mirjam; McMohan, Nicole; Hennessy, Jann; Ngian, Hie Ung; Wong, Jin Shyan; Mohana, Anand; Wong, See Chang; William, Timothy; Mayo, Mark; Baird, Robert W.; Currie, Bart J. (American Society for Microbiology., 2013)
Misidentifications of Burkholderia pseudomallei as Burkholderia cepacia by Vitek 2 have occurred. Multidimensional scaling ordination of biochemical profiles of 217 Malaysian and Australian B. pseudomallei isolates found clustering of misidentified B. pseudomallei isolates from Malaysian Borneo. Specificity of B. pseudomallei identification in Vitek 2 and potentially other automated identification systems is regionally dependent.